A Criatividade no Psicodiagnóstico de Rorschach: Uma Possibilidade de Enriquecimento à Interpretação dos Resultados - Sakamoto, Cleusa Kazue (2003)
The Rorschach Method presents stimuli for the accomplishment of a cognitive structuration task that appeases especially the imagination. Therefore, the generation of answers depends on the objective and subjective aspects that involve attention, perception, logical analysis, decision making processes, in other words: creativity. From this point of view, we selected some results from the Rorschach protocols, so as to direct an initial debate regarding the proposal of creative indicators offered by this method. The perspective of an analysis in which we can verify the presence and quality of the creative capacity on the individual may represent an interesting enrichment to the interpretation possibilities of the psychological profile offered by the Rorschach Psychodiagnosis.